Dietary administration of Pontogammarus maeoticus extract affects immune responses, stress resistance, feed intake and growth performance of caspian roach (Rutilus caspicus) fingerlings - Rudabeh Rufchaei (2018)
© 2017 Elsevier Ltd Dietary administration of immunostimulants showed promising results for elevation of immune responses and disease resistance. The aim of the present study was to investigate the effects of dietary Pontogammarus (Pontogammarus maeoticus) extract on innate immune response, stress resistance, feed intake and growth performance of the Caspian roach fingerling. Two levels of P. maeoticus extract dilution with distilled water 1:25 [T1] and 1:50 [T2] were prepared. Experimental diets were prepared by top-spraying the basal diet with equal amount (2%) of diluted extracts. One hundred and eighty Caspian roach fingerlings (4.30 ± 0.10 g) were supplied, stocked in nine 100-L tanks (three treatment repeated in triplicates) and fed on experimental diets for 8 weeks. At the end of the trial, serum innate immune parameters (Total Ig, ACH50, and lysozyme activity), resistance against salinity stress, feed intake and growth parameters were measured. The results revealed remarkable increase of innate immune parameters and resistance against salinity stress in roach fed P. maeoticus extracts (P < 0.05). Also, growth performance and food intake were notably improved in P. maeoticus extracts fed fish (P < 0.05). These results revealed beneficial effects of P. maeoticus extract on innate immune response, resistance, feed intake as well as growth performance of the Caspian roach.